Empowering Organizational Culture to Increase Senior High School Principal’s Performance - Sutji Harijanto (STKIP Singkawang, 2020)
This study aims to explore the empowerment of organizational culture in increasing the senior high school Principal’s performance. This research used a survey method with a causal approach. The affordable population in this study were 146 heads of public and private high schools in East Jakarta. The sampling technique used is simple random sampling. The data were collected using a questionnaire. The data analysis technique used descriptive analysis and inferential analysis (path analysis). The result shows that the senior high school Principal’s performance can be increased by empowering organizational culture. It also shows that the senior high school Principal’s performance strengthens the notion that the higher score of the independent variables of organizational culture, the higher score of the senior high school Principal’s performance serving as the dependent variable. Strengthening organizational culture will improve senior high school Principal’s performance. Finally, the senior high school Principal’s performance was examined at one point in time. The quality of the principal’s performance will increase if organizational culture also increases.